Expression of genes related to hydrogen peroxide generation and phytohormones in Ganoderma-inoculated oil palm seedlings pretreated with phytohormones and their inhibitors - Durgadevi, Mohan; Parameswari, Namasivayam; Noor Baity, Saidi; Chai-Ling, Ho (Elsevier B.V., 2023)
Hydrogen peroxide, salicylic acid (SA) and jasmonic acid (JA) are reported to play important role in plant defense responses against pathogens. In this study, we analyzed the transcript abundance of oil palm respiratory burst oxidase B (EgRbohB1) and H (EgRbohH), Coronatine Insensitive 1 (EgCOI1), OPR5 (EgOPR5), hypersensitive induced response 1 (EgHIR1) and Nonexpressor of pathogenesis-related (EgNPR1) in Ganoderma boninense-inoculated oil palm roots that were pretreated with SA, JA and their inhibitors, paclobutrazol (PAC) and diethyldithiocarbamate (DIECA), respectively. We showed that EgNPR1 was down-regulated by G. boninense infection in SA-pretreated oil palm roots while EgHIR1 was up-regulated by G. boninense in PAC-pretreated oil palm roots. G. boninense inoculation did not change the gene expression levels of EgOPR5 in JA- and DIECA-treated oil palm roots significantly, compared to the uninoculated oil palms roots that were treated similarly. EgCOI1 was up-regulated by G. boninense in JA- and DIECA-pretreated oil palm roots, respectively. G. boninense up-regulated EgRbohB1 in SA-pretreated oil palm roots but down-regulated it in PAC-pretreated oil palm roots. EgRbohH was also down-regulated by G. boninense in PAC-pretreated oil palm roots. These findings facilitate the understanding of phytohormone effects on oil palm-Ganoderma interaction.